Mystery and Humility in the Depths of Understanding of Reality - Pohar, Borut (Religions, 2023)
The scientific process of understanding natural phenomena such as evolution is an important tool for human progress, so it is good to know where it begins and where it ends, or where it leads. In this article, we put forward the observation that mysticism begins when, in understanding phenomena, we move into the intellectual realm of the unobservable and invisible material and personal life processes, which are interconnected in two ways. On the one hand, the material life processes, which can be contemplated mystically by means of scientific explanations, analogical models, and imagination, are the reason for the purposefulness of identities that are the fruit of personal processes. These are experts, professional and amateur scientists, and lay scientists who are attracted to identity precisely because of the material life processes in which they have an interest, enthusiasm, or passion. On the other hand, it is precisely their mental engagement with these material life processes through the mystical contemplation of the beautiful solutions to nature’s problems that makes them true since truth is classically conceived precisely as the correspondence between intellect and a thing. Discerning the truth of hypotheses, theories, mid-range theories, and meta-theories, however, requires humility at all levels because of the collective way of seeking truth. In this process of truth discernment, it is necessary to accept humbly that I may be wrong and that my neighbor may be right, which ultimately leads us to the mysticism of the Triune God’s merciful love.